Subtansi Hukum Materil Perkawinan Di Lingkungan Peradilan Agama - Jamil, Jamal (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2015)
Material marriage law in the Religious Courts are substances in the implementation of Islamic law itself, because it is not possible in a decision that produced by the Religious Courts without referring to a law enacted by a State. The presence of material law marriage will bring a fresh spirit to implement the Religious Courts authority itself.It has also been discovered, there are three specificity of religious courts. first; as a judicial body for those who Moslem, except for the economic case Shari’ah. second; as judicial implement Shariah law coupled with the laws of the State, the decisions of judges, common law doctrines and others throughout the match or not conflict with Shariah law. third; as a judicial body only enforce the laws that are (in the field) civil law